Unpacking the Quiet Quitting Phenomenon: The Role of Work Stress in the Workload and Work-Life Balance - Ramadhi; Eko Fikriando; Donal Ortega; Barkhia Yunas; Relifra; Destia Ayu Lestari (Journal of Enterprise and Development (JED), 2024)
Purpose: This study explores the role of work stress as a mediator in the relationship between workload, work-life balance, and the phenomenon of quiet quitting among Generation Z employees.Method: The research adopts a quantitative approach, utilizing a random sampling technique. Data were collected from 156 Generation Z employees in West Sumatra through a structured questionnaire designed to assess workload, work-life balance, work stress, and quiet quitting behaviors. The collected data were analyzed using Smart PLS 4.0 to examine the relationships among these variables.Result: The findings found that workload has a significant impact on work stress, while work-life balance does not significantly affect work stress. Similarly, workload significantly influences quiet quitting, but work-life balance does not. Work stress is also found to significantly impact quiet quitting. However, work stress does not mediate the relationship between workload and quiet quitting. In contrast, work stress does mediate the relationship between work-life balance and quiet quitting.Practical Implications for Economic Growth and Development: This study provides practical insights for businesses in West Sumatra to better manage workloads and support work-life balance initiatives. By addressing workload-related stress and fostering a healthier work-life balance, organizations can reduce quiet quitting, thereby improving employee well-being, engagement, and overall productivity. These improvements contribute to sustainable economic growth and development.